Avaliação da contaminação aquática por fármacos utilizando análises ecotoxicológicas - Raquel Sampaio Jacob (2017)
Considerable quantities of different classes of drugs are consumed annually worldwide. After use, these compounds are partially metabolized and excreted. The drugs, once disposed of in a sewage treatment plant, can remain stable even after conventional or advanced treatments, often reaching drinking water sources. Hence, this study aims to evaluate water contamination by pharmaceuticals of different classes, focusing on ecotoxicological analyses. In order to facilitate data appreciation, the thesis is developed in five chapters. Thus, the development of chapter 2 consists of selecting ten pharmaceuticals which had their acute toxicity tested for Aliivibrio fischeri in three formulations (generic drug, similar drug, and brand name drug). In Chapter 3, pharmaceuticals selected from the results of chapter 2 - metformin, simvastatin, diazepam and omeprazole - were submitted to acute toxicity analyses with Aliivibrio fischeri, chronic toxicity with Pseudokirchneriella supcapitata and avoidance test with Cyprinus carpio. With regard to chapter 4, in order to assess synergic and antagonistic effects, the eleven possible mixtures of pharmaceutical compounds had their acute toxicity tested. Finally,chapters 1 and 5 intend to respectively introduce and close the thesis with an integrative approach. Through this work, it has been confirmed that not only pharmaceuticals, but also excipients may be capable of generating environmental imbalance, for those result in acuteand chronic effects and incite evasion of individuals. In addition, unpredictability of pharmaceutical interaction when in mixtures has been clarified, a situation in which a range of phenomena may occur, such as hormesis, synergism and antagonism. In terms of acute toxicity, all compounds generated some damage in Aliivibrio fischeri. In chronic toxicity tests, simvastatin was not toxic, whereas omeprazole was the drug capable of causing deleterious effects at lower concentrations, followed by metformin and dizepam. Finally, about the avoidance test, the drugs omeprazole and especially simvastatin induced an avoidance response in Cyprinus carpio. In light of this, there is no doubt that the presence of the emerging contaminants in water matrices should not be neglected. Although the subject matter is a relevant research topic, it is necessary that the dimension of the problem reaches the managing bodies, duly capable of adopting effective measures to reverse a scenario of such complexity.